Novel copy number variation of the BAG4 gene is associated with growth traits in three Chinese sheep populations. Issue 4 (2nd August 2021) - Yang, Zhaoxin; Cao, Xiukai; Ma, Yilei; Cheng, Jie; Song, Chengchuang; Jiang, Rui; Wang, Xiaogang; Huang, Yongzhen; Buren, Chaogetu; Lan, Xianyong; Ibrahim, Elsaeid Elnour; Hu, Linyong; et al.
Abstract: Copy number variation (CNV) as an important source of genetic phenotypic and variation is related to complex phenotypic traits. The aim of this study was to investigate the potential associations of BAG4 (Bcl-2-associated athanogene 4) copy numbers variations with sheep growth traits in three Chinese sheep breeds (CKS, STHS, and HS). BAG4 is located within the stature and udder attachment quantitative trait loci (QTL) in sheep. Expression profiling revealed that the BAG4 gene was widely expressed in the tissues of sheep. The distribution of BAG4 gene copy number showed that the loss of copy number was more dominant in CKS and HS which was different from that in STHS. Statistical analysis revealed that the BAG4 CNV was significantly associated with body height in CKS ( p < 0.05), with body slanting length in HS ( p < 0.05), and with body height and hip cross height in STHS ( p < 0.05). The χ 2 values showed significant differences in the BAG4 CNV distribution frequency between varieties. In conclusion, the results establish the association between BAG4 CNV and sheep traits and suggest that BAG4 CNV may be a promising marker for the molecular breeding of Chinese sheep.